2006
DOI: 10.1063/1.2337523
|View full text |Cite
|
Sign up to set email alerts
|

Traveling-wave photomixers fabricated on high energy nitrogen-ion-implanted GaAs

Abstract: The authors report on fabrication and measurement of traveling-wave photomixers based on high energy and low dose nitrogen-ion-implanted GaAs. They used 3MeV energy to implant N+ ions into GaAs substrates with an ion concentration dose of 3×1012cm−2. The N+-implanted GaAs photomixers exhibit improvements in the output power in comparison with their counterparts, photomixers fabricated on low-temperature-grown GaAs. The maximal output power was 2.64μW at 850GHz. No saturation of the output power with increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Therefore, commonly used semiconductors for THz generation are defect-rich to reduce the fall time of the transient current. Examples include low-temperature grown or ion-implanted GaAs and silicon (McIntosh et al, 1995;Shan and Heinz, 2004;Krotkus and Coutaz, 2005;Mikulics et al, 2006). Following the pioneering work of Auston (1983), Grischkowsky (1993), and their coworkers, researchers optimized ultrafast photoconductive switches in the past two decades to permit generation and field-resolved detection of electromagnetic transients up to $5 THz.…”
Section: Generation Of Thz Radiation By Photoconductivitymentioning
confidence: 99%
“…Therefore, commonly used semiconductors for THz generation are defect-rich to reduce the fall time of the transient current. Examples include low-temperature grown or ion-implanted GaAs and silicon (McIntosh et al, 1995;Shan and Heinz, 2004;Krotkus and Coutaz, 2005;Mikulics et al, 2006). Following the pioneering work of Auston (1983), Grischkowsky (1993), and their coworkers, researchers optimized ultrafast photoconductive switches in the past two decades to permit generation and field-resolved detection of electromagnetic transients up to $5 THz.…”
Section: Generation Of Thz Radiation By Photoconductivitymentioning
confidence: 99%
“…[4][5][6] Using this technique, we applied 400 mW to our mixers, limited by our optical amplifier, typically illuminating an interdigitated stripline area of 2 lm  150 lm (FWHM). 5,7,8 These intensities were comparable with those of lumped-element mixers, but typically stronger saturation was observed, with two contributions: the sub-linear behavior of the DC photocurrent I ph (P NIR ) with input power (responsivity), explained by thermal effects; and a saturation in addition to the square law dependence of the THz-power on the DC photocurrent, P THz (I ph ). This second contribution varied significantly between mixers of different materials and layer structures.…”
mentioning
confidence: 58%
“…Moreover, no re-absorption could be found in 3 MeV ion-implanted samples. 7,17 To illustrate the magnitude of this effect, for example, we have computed the total THz power losses due to reabsorption from our measured A coefficient at 700 GHz for the thick LT-GaAs sample. The reduction in output power at 400 mW is 55% and the reduction at 1000 mW would be 86%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of all the semiconductor materials that have been studied, GaAs grown by molecular beam epitaxy at low substrate temperatures (LT-GaAs) exhibits favorable characteristics, such as high dark resistivity, high breakdown field strength, ultrashort carrier lifetime, and relatively high carrier mobility simultaneously [5,6]. On the other hand, GaAs wafers implanted with ions such as As + , H + , N + , and O + have also been investigated quite extensively for making photoexcited THz antennas [7][8][9][10][11]. Kang et al [12] and Lederer et al [13] have respectively reported subpicosecond carrier trapping time in oxygen-doped GaAs epilayer and subpicosecond response time in oxygen-implanted GaAs.…”
mentioning
confidence: 99%